Development of Classroom Action Research Modules in Christian Education Subjects - Lustani Samosir; Johari Manik; Dian Purba; Endang Juliati Br. Manullang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to develop a classroom action research module equipped with examples of classroom action research on Christian education. This is motivated by the importance of teachers doing classroom action research to improve learning poses and improve learning outcomes in accordance with the goals of the field of study. From the results of the analysis of the needs of teachers for the importance of knowledge of implementing classroom action research, information was obtained that from 297 teachers of Christian education, 98% stated that it was very important to do classroom action research in the field of Christian education, but did not understand how to do it, it was needed modules as a guide to carrying out classroom action research and examples of classroom action research in the implementation of Christian education. This research uses a 4D model development approach with stages of define, design, develop and disseminate. The results of the research are in the form of classroom action research modules equipped with examples in the learning of Christian Education class VII with the title "Improving the learning outcomes of Christian education through the application of role playing methods at the junior high school level." The results of this study have not been as expected, because in the example of special classroom action research has not been completed until the stage of disseminate because teachers and students teach and learn online due to the Covid-19 pandemic. That is, the modules that have been developed that are followed by examples of their use are constrained, so that only to the limit of product revision. However, this module and example is expected to be able to provide a good understanding for teachers and supervisors of Christian education and become a guide to implement classroom action research to improve the learning process and improve learning outcomes as one of the fields of study aimed at forming the character of a nation that obeys God's orders expressed in a plural social life and respect each other's children.